Facilitating open science practices for research syntheses: PreregRS guides preregistration. (2nd February 2022) - Schneider, Jürgen; Backfisch, Iris; Lachner, Andreas
Abstract: Researchers increasingly engage in adopting open science practices in the field of research syntheses, such as preregistration. Preregistration is a central open science practice in empirical research to enhance transparency in the research process and it gains steady adoption in the context of conducting research synthesis. From an interdisciplinary perspective, frameworks and particularly templates are lacking which support researchers preparing a preregistration. To this end, we introduce preregRS, a template to guide researchers across disciplines through the process of preregistering research syntheses. We utilized an R Markdown template file to provide a framework that structures the process of preparing a preregistration. Researchers can write up the preregistration using the template file similar to filling out a form, with the template providing additional hints and further information for the decisions along the framework. We integrated the R Markdown template in an R package for easy installation and use, but also provide a browser‐based option for users granting low‐barrier access. PreregRS constitutes a first step to facilitate and support preregistration with research syntheses for all disciplines. It further adds to establishing open science practices in conducting research syntheses.